Evaluasi Realisasi Anggaran Dalam Mengukur Kinerja Keuangan Kementerian Desa PDTT Tahun 2017-2022 - Rifa Fairuz Azra (CV. ITTC INDONESIA, 2024)
Poor budget management from the government results in a lot of unrealized budget leftovers, so that the implementation of financial performance cannot run efficiently and effectively. This study aims to examine and describe how the effectiveness and efficiency of financial performance at the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. This research uses Value For Money analysis. The type of data used in this study is secondary data in the form of budget realization data. The sample used in this study is the 2017-2022 Budget Realization Data. This research technique uses quantitative descriptive analysis methods. This study examines the effectiveness and efficiency ratios of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration (Kemendes PDTT) budget expenditures from 2017 to 2022. The results of the analysis show that the level of budget effectiveness in 2017 reached a sufficient level due to austerity policies and budget non-utilization in management support activities. However, in the 2018-2022 period, the level of effectiveness increased to very effective although there was an insignificant percentage decrease in 2020 and 2021. On the other hand, the efficiency ratio of budget absorption showed a significant increase during the period. In 2017, budget absorption was considered inefficient, but from 2018 to 2022, the efficiency value continued to increase and reached a very efficient level, although it experienced a slight decrease in 2020 and 2021 before increasing again in 2022.Overall, the results of this study conclude that MoV has successfully implemented a budget with a good level of effectiveness and efficiency during the 2017-2022 period. Thus, budget management in the Ministry is considered effective and efficient in the use of available financial resources.